Examining the interplay of teacher well-being, executive function, and adaptability in virtual instruction during COVID-19 disruptions - Garcia, Aileen S.; Jeon, Shinyoung; Kwon, Kyong-Ah; Horm, Diane M. (Frontiers in Education, 2024)
The documented challenges of the early care and education (ECE) workforce include poor well-being, inadequate compensation, and high turnover rates. The COVID-19 pandemic not only exacerbated these issues, but also imposed additional demands such as virtual instruction, highlighting the need to understand how teachers' well-being relates to their adaptability in teaching. The present study examined whether early childhood teachers' wellbeing is directly and indirectly related to adaptability to virtual instruction via teachers' executive function during the COVID-19 pandemic. With a research-practice partnership project in a Head Start program in a metropolitan area in the central United States, data were collected from the Early Head Start/Head Start annual teacher survey (n = 148). Mediation analysis showed that teachers who demonstrated higher well-being displayed higher levels of executive function, which in turn was associated with greater adaptability in virtual instruction. Beyond the pandemic, findings highlight the importance of supporting teachers' well-being and executive functions to promote adaptability, which is critical not only in virtual instruction, but also in successfully navigating other challenges of the teaching profession.